Narodne manjšine v Sloveniji 1920-1941 - Komac, Miran (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2015)
The article deals with the status of the Hungarian and German ethnic minorities in Slovenia between 1920 in 1941. Their settlement territory is presented with statistical data. The author draws attention to several discriminatory practices experienced by the members of these two ethnic minorities, for example in relation to the agrarian reform, admission to minority language schools, Slovenization of place names, etc. Such practices created a distance between the members of ethnic minorities, the majority nation, and Slovenia. Thus, it was not unusual for members of ethnic minorities, Germans in particular, to become fond of extreme nationalist movements - Nazism, which at the end of the war brought about their ethnic disappearance.
Keywords: Slovenia; Slovenija; narodne manjšine; Madžari; Nemci; Judje; cigani; Romi; asimilacija; assimilation; etnična distanca; 1920-1941